Dança em ação: política de resistência no Encarnado de Lia Rodrigues - Guzzo, Marina Souza Lobo (2009)
Art is a form of communication between artists and interlocutors that relate to each other through a network of people, things, strengths and senses, in an experience of sharing the sensible. This shared experience may have political and transforming effects, understanding political as something beyond the exercise of power or government, but as an activity that organizes people, things, circulations and ways of doing. The proposal of this research was to understand how is the political sense constructed for a work of art by taking a contemporary spectacle of dance, "The Incarnate" by Lia Rodrigues as an example. We start with the assumption that a dance spectacle acts as a network of materialities and socialities and the political senses are built after a series of happenings and actors, which characterize the changing potency of the work. The methodology used in this research was made with the contributions of the Actor-Network Theory, as an effort of systemization of a form of thinking and handling reality, which, instead of interpreting the world, tries to describe it by taking its hybridization under consideration. The Networks from "The Incarnate" were analyzed with the description (or a version of it) of the dance spectacle, of its characters, its actors, materialities, places, leaving the part of the researcher as the one that evidences different tellings regarding the spectacle, after the questions and issues with the actors. The political action was compared to weaving, which can only develop itself after a group of parallel and preparatory actions, connected between themselves as the warp, the plot. Thus, "The Incarnate" was presented as a network that, with diverse plots (aesthetic and thematic choices, the acting of the choreographer / dancer in relation to his own work or to public policies of dance, the choice of spaces and places of practice, research, creation and presentation of the works and resonances and repercussions with public and critic) makes visible the invisible, reinventing speeches and places to resist in the present